Prawne uwarunkowania kampanii wyborczych - Korycki, Krzysztof (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The article concerns the legal conditions relating to the election campaign. It discussed issues concern in particular the concept and timing of the election campaign, elec-tioneering, election material, dissemination of false information and campaign programs radio and television broadcasters. The text takes into account all the relevant amendments to the Election Code and the jurisprudence of the Constitutional Court.